EVALUATING CHPE OUTCOMES IN ALLIED HEALTH SCIENCES FACULTY: A MULTICENTER PRE–POST STUDY IN PESHAWAR - DR. MUHAMMAD SULEMAN , DR. MUHAMMAD AAMIR SARDAR, DR. MENHAS , DR. MUNEEBA GHAFOOR , DR. BEHRAM ASIM (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background: Faculty development Faculty development is a pressing area of the sphere of Health Professions Education improvement, yet, at the majority of the establishment, the programs of faculty development are not context-specific and designed to the sphere of Allied Health Sciences (AHS) faculty. The Certificate in Health Professions Education (CHPE) is an intervention program that is based on the competence in faculty teaching improvement, assessment and educational technologies improvement. Purpose: The goal of the study is to explore the impact that a CHPE program has on the knowledge of the faculty at the Allied Health Sciences at Peshawar region in Pakistan and their perceived teaching practice. Methods: The study was a quasi-experimental pre-post intervention multicenter study that was carried out under the Peshawar area in both the public and the private institutions from October 2024 to June 2025. The sample size of CHPE program faculty of the Allied Health Sciences (n= 65) was used as purposive sample. They have been collected on the ground of (1) self-perception questionnaire in a structured form (31 items) which examined the teaching strategies, assessment competencies and online teaching tools, and the task content was proven to be validated through expert (CVI/CVR) review, pilot testing and reliability testing (Cronbachs alpha [?] of 0.70 acceptable); and (2) pre and post-tests with one-best-answer MCQs (10 marks per module) module-specific. The toleration of the data and its calculations were done with SPSS and safe computer tools. Paired t-test or Wilcoxon signed-rank tests would be used in pre-post comparisons to establish the outcome of knowledge and McNamara / McNamara-Bowker test would be used to establish the results through the help of paired categorical perception. It would have a level of statistical significance of p < 0.05 and the conveyed effect sizes (Cohen d or r). Findings: The pilot estimates finding of a sample study of 65 participants indicate that the sample will comprise of about 49 (75.4) females and 16 (24.6) males, 36 (55.4) with lecturer qualification and 39(60.0) with master’s degree. It is expected that the anticipated changes in the self-perceived instruction practice would be the subsequent decrease in the level of confidence in the lesson plan preparation (58 to 43), the interactive lectures (65 to 47), case-based learning (34 to 29), the flipped classroom (34 to 25) and online teaching (58 to 44) that would be associated with the enhancement of the level of self-reflection and the understanding of the skills deficiency. The perception related to the evaluation will also alter because the confidence in the creation of OSCE/OSPE stations (48 to 43) and the choice of the teaching tools (55 to 47) will drop. The results will be based on the observed pre/ post module test scores to form the knowledge outcomes and expected to improve over modules as observed in previous CHPE cohorts. Conclusion: CHPE program will result in elevated educational level and enable the faculty of Allied Health Sciences to conduct critical self-reflection. The analysis and multicentre implementation underway with sufficient sample size will augment the conclusions made concerning the effectiveness of faculty training on the targeted area of Peshawar. The longitudinal follow-up is suggested in order to measure the sustained change in the institutional effects and teaching behaviours.